In vitro evaluation of aqueous leaf and peel extracts of Musa species for low-input management of fungal leaf spots of sweet potato (Ipomea batatas Linn.) - Amarachi G Nwaogu; Florence T Obani; Faith N Iheanacho; David Nwazuo Enyiukwu (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2022)
Sweet potatoes are important food staples in tropical sub-Saharan Africa. Orange flesh sweet potato (OFSP) varieties are especially important for combating vitamin A deficiencies and nutrition-induced blindness. Fungal leaf spots are one of the many challenges constraining its production in Umudike, Southeast, Nigeria. The aims of this experiment were to isolate the causal fungi of leaf spots of OFSP and to attempt their control using aqueous extracts of banana peels, plantain peels and plantain leaf in vitro. Mycotic agents isolated from infected plant were Verticillium longisporum, Rhizoctonia solani, Penicillium chrysogenum and Aspergillus niger. Pathogenicity test conducted on the organisms revealed that the first three pecies were actively pathogenic, with infected sweet potato showing irregular brown spots/blights surrounded by chlorotic hallo around leaf veins and margins of the laminae; while A. niger showed weak infection of the plant. In the laboratory, four concentrations (10%, 25%, 50% and 75%) of ripe and unripe plantain peels, ripe and unripe banana peels, and senescent and new plantain leaves, griseovid® (a standard antifungal) and control (sterile water) were evaluated in vitro for inhibition of mycelial elongation of the test myco-pathogens associated with the leaf spot disease of the crop. The experiment was laid out as 3 x 4 x 8 factorial in CRD with 3 replications. The botanicals significantly (P≤0.05) and differentially retarded radial growth of the fungus over the control in a dose-dependent manner. However, the fungitoxicity of the botanicals were inferior but compared favourably with the standard antifungal griseofulvin (griseovid®). Exploiting the potency of these readily available, cost effective and eco-friendly agro-wastes against these fungal pathogens causing leaf blight of sweet potato will not only reduce the hazards and pollution challenges associated with use of synthetic pesticides but also increase food production in developing countries where synthetic fungicides are expensive and out of reach of low-input farmers.